Program Bimbingan Belajar Gratis “Bimbel Calistung” untuk Anak-anak di Sekolah Pulau Pari berikan Program Bimbingan Belajar Secara Gratis Kepada Anak-anak di Sekolah Pulau Pari “Bimbel Calistung” - M. Saleh, Mega; Handayani, Sri Lestari; Uslan, Uslan (Jurnal SOLMA, 2023)
Background: Calistung Tutoring is a basic capability that a person needs to have so that he can learn other things more easily. For example, at school, children must be able to read, write and also count. The aim of this program is to provide an effective Calistung tutoring program to children at school. Method: Guiding children to improve their understanding and abilities in calistung tutoring for children at school and the targets for this activity are 25 students spread across class 1 of Pari Island Elementary School 01. Results: The students have high enthusiasm for learning calistung tutoring but There is a lack of creating an interesting and stimulating reading environment in schools and in the community, so creating an attractive environment for students can be done by providing a diverse collection of books that suit the students' interests. Conclusion: By implementing the right strategy and carrying out regular evaluations, the Calistung tutoring program can be an effective means of forming a generation that likes reading, writing and arithmetic and has strong skills for its students.